Answer:
y + 1 = -
(x - 4)
Explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
y = 3x + 5 is in this form
with slope m = 3
Given a line with slope m then the slope of a line perpendicular to it is
= -
= -
![(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o08xg954t1gbzo9avralvfomcybk63rm02.png)
The equation of a line in point slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line
here (a, b) = (4, - 1), thus
y - (- 1) = -
(x - 4), that is
y + 1 = -
(x - 4) ← in point- slope form